Contribuições da morfodinâmica no zoneamento territorial em Goiana, litoral norte de Pernambuco, Brasil - Madruga, Marcelo Menezes Diniz (2022)
This research carried out the analysis of the morphodynamic characteristics of the coastal cord formed by Barra de Catuama, Catuama, Ponta de Pedras and Carne de Vaca beaches, located on the northern coast of the State of Pernambuco, in Goiana city. The approach adopted was based on the bimonthly collection of topographic profiles of the beaches and sedimentological sampling in three sectors of the beach, which were carried out between the months of July 2017 and May 2019. The coastal cord studied. Bathymetry was accomplished in the studied area and thus the closing depth of the shallow continental shelf was determined. With this, it was possible to define the maximum high tide line and establish the non-edifying zone. The comparison of the surveyed topographic profiles indicated that the sedimentary balance was positive (deposition) in only one point of the studied littoral cord. Profile P4, surveyed on Ponta de Pedras beach, showed the smallest volume variation (- 6.27m³/m), despite being an intensely occupied stretch. The correlation of the topographic profiles with the sedimentological analysis allowed us to identify the influence of the Itapessoca and Goiana rivers on the P2, P3 and P7 profiles. Profiles P1, P2, P3 and P7 have quartz composition. However, the profiles P4, P5 and P6 are composed predominantly in the shoreshore sector by carbonate sediments, mainly by halimedas. For the hydrodynamic characterization, the area was subdivided into five sectors and a non-edifying zone was established for each sector. For each sector, an optimistic and pessimistic estimate of the sea advance until 2100 was made. All sectors had a non-building zone area greater than the 33 meters stipulated by law, with sector 1 being the largest of them, with 303.37 m of retreat in the pessimistic estimate